The Risk of Mixed Laws: The Example of Indirect Agency under Chinese Contract Law - Ling, Bing; Wolff, Lutz-Christian (Columbia Journal of Asian Law, 2002)
In recent years mixed jurisdictions have become a subject of considerable academic discussion. The term mixed jurisdictions is generally used for legal systems which are based on different legal traditions. The analysis of mixed jurisdictions normally refers to the development and operation of mixed legal systems. The mixing of structures and legal institutions from different backgrounds, however, is not only a development of the past. On the contrary, due to the trend towards internationalization all legal systems of the world are mixing in one way or another. Due diligence now requires legislative bodies to study foreign and international models when creating new laws in order to learn from other countries’ experience and to find the most suitable legislative solution. In practice, legislators, especially in emerging legal systems, usually look at legal structures which have already proven successful in other jurisdictions in order to avoid the painful experience of discovering legislative deficiencies only after the enactment of a new law. Sometimes laws which are already in force abroad are taken over in toto. Other times drafters of new legislation decide to adapt various concepts derived from different foreign systems, i.e. to ‘mix’ them, in order to combine their advantages by way of ‘legislative cherry picking. In the latter case, the characteristics of mixed jurisdictions are mirrored on a micro level in the new ‘mixed law’.